IMPLEMENTASI CONVENTION ON THE ELIMINATION OF ALL FORMS OF DISCRIMINATION AGAINST WOMEN (CEDAW) DI INDONESIA - Anita Putri Rukayah Siregar; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Violence against women is already being world issue, where women’s rights are not fulfilled and discrimination against women happened on some aspects of life. To reduce the number of violence against women and eliminate any forms of discrimination against women, UN created a convention called Convention on The Elimination of All Forms of Discrimination against Women (CEDAW). Indonesia ratified this convention in 1984, but in the following years after ratification, the number of violence against women keeps increasing especially on domestic violence case. In 1998, Indonesia’s President BJ Habibie founded National Commission of Women (Komnas Perempuan) as National Human Rights Institute (NHRI) in Indonesia that works as the national correctional system, and monitoring enforcement of women’s right, with CEDAW as its work foundation. The sources of this research were obtained through literature reviews, journals, books, articles, websites, and others. This research used qualitative methods and generating descriptive data. In terms to solve the problem, this research is using the Socialist Feminism perspective with assume that socialist feminism is the most appropriate perspective to describe women’s issue especially in domestic violence case where patriarchy and capitalism are the main problem that caused domestic violence against. This research is using Constructivism theory where CEDAW is the main convention that constructed in Indonesia and Komnas Perempuan) that implementing CEDAW in Indonesia as the level of analysis. Human’s Rights is used as the concept where feminism is created by those issues. This research shows that implementation forms of CEDAW by Komnas Perempuan to raise and increase women’s awareness, especially in domestic violence that being the main issue, are; formulating laws on the elimination of domestic violence, releasing annual report of violence against, supporting Indonesia’s women movements and releasing journals and books about domestic violence. Key Words: CEDAW, Discrimination, Domestic Violence, Women’s Rights, Komnas Perempuan.